Application of Digitalization Through E-Court as Renewal of Administrative Law Procedure in Indonesia - Fatria Khairo (International Journal of Artificial Intelligence Research, 2022)
Based on Law Number 48 of 2009, justice must be done quickly and cheaply. The embodiment of this law is carried out by implementing Electronic Courts. The State Administrative Court can implement Electronic Court (E-Court) by empowering the already owned resources. This study aims to look at the application of digitization through the implementation of Electronic Courts as a renewal of the State Administration procedural law. The method used in this study is the statute approach and the conceptual approach. The data used in this study comes from the results of previous research and existing legislation in Indonesia. The results of this study found that information technology greatly supports the implementation of E-Court. Partial E-Court can be carried out electronically by issuing a Supreme Court Regulation. As for the full implementation of E-Court, we still have to wait for changes to the procedural law through changes to the State Administrative Court Law